Physical Fitness and Motor Competence in Chinese and German Elementary School Children in Relation to Different Physical Activity Settings - Andreas Hohmann; Xinchi Yuan; Manfred Schmitt; Hui Zhang; Micha Pietzonka; Maximilian Siener (MDPI AG, 2021)
(1) Background: Children with greater physical activity (PA) may show a higher physical fitness (PF) and motor competence (MC) compared to peers with less PA. The purpose of this study was to examine the relationship between moderate-to-vigorous physical activity (MVPA), PF, and MC in 8- to 9-year old children in Germany and China. MVPA was differentiated into five PA settings: family sport, club training, school sport, leisure sport, and outside play. (2) Methods: This longitudinal study comprised N = 577 children (n = 311 girls, n = 266 boys) who were studied over a one-year period. Each child's PF and MC was determined using sports motor tests. The children's PAs were measured using a questionnaire. (3) Results: The children's PA was positively associated with PF and MC. The MVPA-settings: family sport, leisure sport, outside play, school, and club sport, explained between 18 and 23 percent of the variance in selected PF and MC characteristics in a multivariate linear regression analysis. (4) Conclusions: An increase in the children's MVPA might be an appropriate aim in the school sport in Germany as well as in the club sport system in China. Furthermore, family sport should be enhanced in Germany and outside play activities in China, respectively.